Behcet disease: an undifferentiating and complex vasculitis. (2nd January 2023) - Pak, Daniel; Park, Hyon Ju
ABSTRACT: Behçet Disease is a relapsing and remitting variable vessel vasculitis characterized by recurrent mucocutaneous ulcers that can involve almost every organ system in the body. Indeed, the presence of recurrent oral or genital ulcers with other auto-inflammatory symptoms should raise suspicion for this elusive disease. It is unique among the vasculitides in that it can affect vessels of small, medium, and large size and tends to involve venous rather than arterial circulation, and its effects on the pulmonary venous circulation are particularly notable for their role in disease mortality. Classically seen in Mediterranean, Middle-Eastern, and eastern Asian countries, and relatively rare in the United States, prevalence has been increasing, prompting an increased need for internists to be aware of Behcet's clinical presentation and treatment. As early recognition and diagnosis of the disease is key to successful treatment and better prognosis, this review provides a brief summary of the current etiological theories, important clinical manifestations, and treatments including newer biologic alternatives.